The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1010539516684534
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Birth Survey of the Fukushima Health Management Survey

Abstract: The Pregnancy and Birth Survey was started by Fukushima Medical University as part of the Fukushima Health Management Survey in 2011 in order to assess the physical and mental health of mothers and provide parenting support (telephone counseling) for those in need. The present study reviewed the major findings from 4 annual surveys conducted from 2011 to 2014. Overall proportions of preterm deliveries, low birth weight infants, and congenital anomalies in the first year were almost the same as those in nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
1
15
2
Order By: Relevance
“…The proportion of female students reporting depressive symptoms in Fukushima was quite high. This was inconsistent with the findings of prior studies assessing mothers with infants in Fukushima, in which rates of depression ranged from 23.4% to 27.1% based on results obtained via a 2-item screening instrument [ 4 ]. The rates reported in the present study were much higher, even in comparison to previous reviews [ 34 , 35 ] and data obtained from young mothers at the time of the Fukushima nuclear accident [ 4 , 8 ].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The proportion of female students reporting depressive symptoms in Fukushima was quite high. This was inconsistent with the findings of prior studies assessing mothers with infants in Fukushima, in which rates of depression ranged from 23.4% to 27.1% based on results obtained via a 2-item screening instrument [ 4 ]. The rates reported in the present study were much higher, even in comparison to previous reviews [ 34 , 35 ] and data obtained from young mothers at the time of the Fukushima nuclear accident [ 4 , 8 ].…”
Section: Discussioncontrasting
confidence: 97%
“…A subsequent tsunami hit the Tokyo Electric Power Company’s Fukushima Daiichi Nuclear Power Plant, causing leakage of radioactive material from the plant. Exposure to both natural and man-made disasters is associated with long-lasting psychological problems [ 1 , 2 , 3 , 4 , 5 ]. Using data derived from the Pregnancy and Birth Survey from the Fukushima Health Management Survey (FHMS) targeting mothers (median age = 30 years) with infants, it was found that 28% of the sample of 2262 women screened positive for depression in 2011 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on birth outcomes following the Fukushima disaster have produced mixed results, with some studies finding no significant changes in birth outcomes in areas affected by the nuclear disaster [30,31,32], and others finding increased proportions of low birthweight and preterm births [33]; however, most studies to date have only assessed outcomes within the first year of the disaster. The overall inconsistency within results from Fukushima, and between results from Fukushima and other disasters where increases in low birthweight or preterm births have been predominant indicate that the effects of this disaster may differ from those observed in other settings [9,10,11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited understanding of maternal and perinatal health following this disaster. There has been mixed evidence for immediate post-disaster changes in birth outcomes; some previous studies have found no increased proportions of low birthweight or preterm births in areas affected by the earthquake and tsunami [29], or in areas additionally affected by the nuclear disaster [30,31,32], in the first year post-disaster. However, there have also been findings of a slight increase in low birthweight neonates to women that had been 28–36 weeks pregnant at the time of the earthquake, in earthquake- and tsunami-affected areas [29], and increased proportions of low birthweight and preterm birth to women who conceived within six months post-disaster in areas affected by the Fukushima nuclear disaster [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation